Cloning and expression analysis of pathogenesis-related protein 1 gene in maize - WANG Jing; LIU Li; ZHANG Zhi-ming; ZHAO Mao-jun; PAN Guang-tang (浙江大学学报. 农业与生命科学版, 2012)
By reverse transcription-polymerase chain reaction (RT-PCR), an open reading frame of pathogenesis-related protein 1 (PR1) was isolated from inbred line R15 which was resistant to kernel rot, named ZmPR1. Molecular and bioinformatic analyses of ZmPR1 revealed that an open reading frame of 528 bp was predicted to encode a 175-amino acid protein with a deduced molecular mass of 18.7 ku. Homology analysis showed that the deduced amino acid sequence of PR1 protein in maize had a high similarity with other higher plants, such as Oryza sativa, Triticum aestivum, and Arabidopsis. PR1 proteins from different plants had the same conservative structure domain of cysteine-rich secretory protein (CAP). The recombinant expressed plasmid pET32a(+)-ZmPR1 was expressed in Escherichia coli BL21. The expression conditions were optimized by induction at different time, different temperature, and different IPTG concentrations. The results indicated that the expression products migrated at the size of 39 ku by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot analysis. The optimum expression condition was 0.6 mmol·L-1 IPTG at 28 ℃, but the induction time has little effect on the expression. The successful expression of ZmPR1 provides some basis for protein purification and preparation of the monoclonal antibody.